An Innovative Synbiotic Formulation Decreases Free Serum Indoxyl Sulfate, Small Intestine Permeability and Ameliorates Gastrointestinal Symptoms in a Randomized Pilot Trial in Stage IIIb-IV CKD Patients - Carmela Cosola; Maria Teresa Rocchetti; Ighli di Bari; Paola Maria Acquaviva; Valentina Maranzano; Simone Corciulo; Agostino Di Ciaula; Domenica Maria Di Palo; Flavia Maria La Forgia; Sergio Fontana; Maria De Angelis; Piero Portincasa; et al. (Toxins, 2021)
Proteolytic dysbiosis of the gut microbiota has been recognized as both a typical feature of chronic kidney disease (CKD) and a risk factor for its progression. Blood accumulation of gut-derived uremic toxins (UTs) like indoxyl sulfate (IS) and p-cresyl sulfate (PCS), intestinal permeability and constipation are typical features accompanying CKD progression and triggering chronic inflammation. In order to verify the efficacy of the innovative synbiotic formulation NATUREN G® in modulating the levels of circulating UTs, intestinal permeability and gastrointestinal symptoms, we set up a randomized, single-blind, placebo-controlled, pilot trial in stage IIIb-IV CKD patients and in healthy controls. Two-month administration of the synbiotic resulted in a decrease of free IS, as compared with the placebo-treated arm, only in the CKD group. The other UTs did not significantly change, although different trends in time (increase in the placebo arm and decrease in the synbiotic arm) were observed. Moreover, after supplementation, reduction of small intestinal permeability and amelioration of abdominal pain and constipation syndromes were observed only in the CKD group. The obtained results suggest the specificity of action of NATUREN G® in CKD and justify further validation in a wider study population.